2007
DOI: 10.1111/j.1365-2702.2007.01994.x
|View full text |Cite
|
Sign up to set email alerts
|

A structured literature review of pain assessment and management of patients with chronic kidney disease

Abstract: Findings from the literature review highlight specific difficulties relating to effective pain control in patients with chronic kidney disease. Research is required to identify and overcome barriers to effective pain management, including the development of specific tools to facilitate interventions that optimize analgesic outcomes in patients with chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 97 publications
1
26
0
1
Order By: Relevance
“…Clearly, the consumers’ experiences demonstrated that prescribers did not want to cause harm to the consumer which affected their pain management. These findings are similar to the limited research into pain management in patients in end stage kidney disease where the prevalence of pain is common and analgesics were underprescribed (Davison 2003, Williams & Manias 2007a). In addition, consumers were hesitant to take analgesic medicines because of their comorbid conditions, a fear of adverse effects and addiction, and pill burden.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Clearly, the consumers’ experiences demonstrated that prescribers did not want to cause harm to the consumer which affected their pain management. These findings are similar to the limited research into pain management in patients in end stage kidney disease where the prevalence of pain is common and analgesics were underprescribed (Davison 2003, Williams & Manias 2007a). In addition, consumers were hesitant to take analgesic medicines because of their comorbid conditions, a fear of adverse effects and addiction, and pill burden.…”
Section: Discussionsupporting
confidence: 83%
“…2005). A literature review examining studies of pain control in kidney disease found that the risk of analgesic‐induced morbidity dominated over an interest in pain relief in patients on dialysis, significantly affecting their quality of life (Williams & Manias 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…There has been recognition that pain is a significant problem in other non-curative conditions such as the human immunodeficiency virus (HIV) (2,3), multiple sclerosis (MS) (4), end stage cardiac disease (5), end stage renal failure (6), and advanced chronic obstructive pulmonary disease (COPD) (7), amongst others. As such, the management of pain within the palliative care field has become a broader issue, and the expertise within the palliative care professionals, much of which has been gained with cancer patients, is now extending into other areas.…”
Section: Introductionmentioning
confidence: 99%
“…Pain in patients with multiple comorbidities contributes to impaired well being, poor physical function, depression, quality of care, and health care overutilization (4)(5)(6)(7)(8). Chronic pain is reported to be prevalent in ESRD (9)(10)(11)(12)(13), but is less commonly studied in predialysis CKD (12,13). The causes of chronic pain across the spectrum of kidney disease are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain often leads to analgesic use (14), but some of these medications' prescription and dosing require special consideration with impaired renal function (11)(12)(13). Prescription and over-the-counter (OTC) purchase of nonsteroidal anti-inflammatory drugs (NSAIDs) are more common in CKD than desirable because they are considered nephrotoxic (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%